Heritage corridors : sustainable tourism development alongside the Silk Road - Szatmári, Sándor (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
Over the centuries several routes have been created alongside geographical corridors. People travelled and traded along these routes, later cities and cultures have emerged on the nodes of them. This phenomenon can be observed on any continent.The Silk Road is a glaring example of this. The system of the Silk Road heads through deserts, seashores, river valleys and mountain passes. It cuts across the Eurasian Continent. The countries along the historical Silk Road look for the opportunities of collaboration and cooperation. We can say, that this cooperation means a natural way of cooperation for these countries from the point of their geographical location and geological connections.A possible way of cooperation is the common tourism development. For this area, the natural geographical and built environment, the connections of these environmental factors have a large importance. The connecting of these circumstances can make a sus-tainable tourism development model. Any countries on the Silk Road have the opportu-nity to invest and connect to this cooperation. It means a sure and long run investment
Keywords: Jedwabny Szlak; turystyka; zrównoważony rozwój; dziedzictwo